Killing Cynthia Ann : a novel - Brashear, Charles (Texas Christian University Press, 1999)
Abducted by Indians as a child, Cynthia Ann Parker refuses to return to the white world, becoming the wife of a Comanche chief with whom she has three children. Captured by Texas Rangers, she is forcibly removed and fails in her attempt to escape.